The economic costs of biological invasions in Africa: a growing but neglected threat? - (:unkn) unknown (My University, 2021)
Biological invasions can dramatically impact natural ecosystems and human societies. However, although knowledge of the economic impacts of biological invasions provides crucial insights for efficient management and policy, reliable syntheses are still lacking. This is particularly true for low income countries where economic resources are insufficient to control the effects of invasions. In this study, we relied on the recently developed "InvaCost" database - the most comprehensive repository on the monetised impacts of invasive alien species worldwide - to produce the first synthesis of economic costs of biological invasions on the African continent. We found that the reported costs of invasions ranged between US$ 18.2 billion and US$ 78.9 billion between 1970 and 2020. This represents a massive, yet highly underestimated economic burden for African countries. More alarmingly, these costs are exponentially increasing over time, without any signs of abatement in the near future. The reported costs were mostly driven by damage caused by invaders rather than expenses incurred for management. This trend was highly skewed towards a few regions (i.e. Southern and Eastern Africa) and activity sectors (i.e. agriculture) and incurred by a small number of invasive taxa (i.e. mainly three insect pests: Chilo partellus, Tuta absoluta, Spodoptera frugiperda). We also highlight crucial, large gaps in current knowledge on the economic costs of invasions that still need to be bridged with more widespread research effort and management actions across the continent. Finally, our study provides support for developing and implementing preventive measures as well as integrated post-invasion management actions at both national and regional levels. Considering the complex societal and economic realities in African countries, the currently neglected problem of biological invasions should become a priority for sustainable development.
Keywords: African Research